Combustible ice mimicking behavior of hydrogen-bonded organic framework at ambient condition - Yang Wang (Nature Portfolio, 2020)
Porous materials function as sorbents for gas storage but release of guest molecules often needs extra energy. Here the authors report reversible methanol adsorption and release in a hydrogen-bonded organic framework, which mimics combustible ice behavior but under ambient condition.